DETERMINATION OF PLUMBUM (Pb) SEAWEED Sargassum sp. AND Eucheuma spinosum IN WATER PUNTONDO REGENCY OF TAKALAR SOUTH SULAWESI - Rahmawati Rahmawati; Mujahidah Basarang (Marina Chimica Acta, 2017)
Seaweed is a low-grade plant that forms the thallus of the thallophyta division (leafless structure). In Takalar district especially in puntondo waters is a seaweed producing area, such as red seaweed (Eucheuma spinosum) and brown seaweed (Sargassum sp). The presence of lead (Pb) in aquatic bodies can come from natural sources and from human activities. However, as industrial and transport usage increases, lead concentration (Pb) in nature can increase. The purpose of this research is to know the content of lead metal (Pb) in some seaweed in Puntondo waters of Takalar Regency. This research is laboratory observation by using sampling technique of Aciddental Sampling. The object of this research is 4 (four) seaweed samples examined (Pb) level in Chemical Laboratory Faculty of Saintek UIN Alauddin Makassar. The results showed that there was Pb concentration in RLM 1 sample 1.7024 mg / kg. In RLM 2 samples there was Pb level of 0.1686 mg / kg. In RLC 1 samples, there was Pb content of 0.99 mg / kg, and in the sample RLC 2 there is a level of Pb as 1.1686 mg / kg. From this result obtained the highest result of Pb on RLM 1 sample that is 1,7024 mg / kg, and the lowest Pb level in RLM 2 sample that is 0,1686 mg / kg.